Financial Performance Analysis: Manufacturing Companies In Indonesia Before And Post The 2008 Global Economic Crisis - Rohmat Hidayat, Agus; Alifah, Nur; Oga Laksana, Medika (Green Publisher Indonesia, 2022)
This study aims to analyze the financial performance of Indonesian manufacturing companies before and after the global economic crisis in 2008. In this study, financial performance is measured by Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). By comparing the average ROA, ROE, and NPM before and after the crisis, the results of the descriptive analysis were tested. It can be seen that ROA, ROE and NPM after the crisis were higher than before the crisis. As a result, post-crisis financial performance has improved compared to before the crisis. Based on the descriptive analysis, it is known that the financial performance of manufacturing companies after the crisis is better than before the crisis. Based on the t test, the results of ROA, ROE and NPM tests were obtained as follows. First, Post-crisis ROA is higher than before the 2008 global economic crisis, and the increase is said to be large. Second, post-crisis return on equity appears to be higher than before the global economic crisis, but this is not statistically significant. Third, post-crisis NPM also appears to be larger than before the crisis, but not statistically significant. The results of the t test show that financial performance as measured by ROA has improved after the crisis compared to before the crisis.